A scoping review on the impact of women’s global leadership: evidence to inform health leadership - Anna Kalbarczyk; Rosemary Morgan; Kelly E Perry; Katherine Banchoff; Charlotte Pram Nielsen; Anju Malhotra (BMJ Global Health)
Introduction The documented benefits of gender parity in leadership are emerging—women leaders have been shown to have a positive impact on maternal and health care policies, strengthen health facilities, and reduce health inequalities. More research is needed, however, to document their impact on global health. We go beyond the well-documented barriers that uphold the lack of gender parity by identifying areas where women leaders are making an impact to inform investment, programming, and policy.Methods We conducted a scoping review of peer-reviewed literature, following Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews (PRISMA-ScR) guidelines, to map evidence on the impact of women’s leadership in organisations in low- and middle-income countries. As many leadership outcomes are cross-disciplinary, outcomes were explored across sectors with particular attention paid to the relevance of these outcomes for global health.Results 137 articles were included in the review. Studies found women leaders’ positive influence on six areas of impact: (1) financial performance, risk, and stability, (2) innovation, (3) engagement with ethical initiatives, (4) health, (5) organisational culture and climate outcomes, and (6) influence on other women’s careers and aspirations. Articles reporting mixed results focused on multiple indicators and still largely pointed to positive results, particularly when modified by other factors including increased education, increased experience, and opportunities to work with other women across the organisation. In all sectors, across leadership roles, and across geographies, women’s leadership can produce positive results. Women leaders’ success, however, cannot be separated from the contexts in which they work, and unsupportive environments can affect the extent to which women leaders can have an impact.Conclusion Increased and sustained investment in women’s leadership within the health sector can lead to improved outcomes for organisations and their clients. Such investments must not only target individual women, but also seek to foster organisational cultures that promote and retain women leaders and support their independent decision-making.